2022
DOI: 10.3390/v14081635
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Amyloid Fibers: Accumulation, Biological Relevance, and Regulation of Higher-Order Prion Architectures

Abstract: The formation of amyloid fibers is associated with a diverse range of disease and phenotypic states. These amyloid fibers often assemble into multi-protofibril, high-order architectures in vivo and in vitro. Prion propagation in yeast, an amyloid-based process, represents an attractive model to explore the link between these aggregation states and the biological consequences of amyloid dynamics. Here, we integrate the current state of knowledge, highlight opportunities for further insight, and draw parallels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…It has been suggested that excess Hsp104 results in aggregate stability (Ness et al, 2017). Conversely, Hsp104 overexpression could unbalance the proper co-chaperone stoichiometric ratio required to form functional Hsp104/70/40 complexes, thereby decreasing fragmentation necessary for prion propagation (Winkler et al, 2012;Naeimi and Serio, 2022). We show that TTR aggregates sediment in higher molecular weight fractions occasionally with Hsp104 OE (Figure 3A) and consistently with Hsp104 A503S (Figure 4C).…”
Section: The Formation Of the Ttr Aggregate And The Role Of Hsp104mentioning
confidence: 63%
“…It has been suggested that excess Hsp104 results in aggregate stability (Ness et al, 2017). Conversely, Hsp104 overexpression could unbalance the proper co-chaperone stoichiometric ratio required to form functional Hsp104/70/40 complexes, thereby decreasing fragmentation necessary for prion propagation (Winkler et al, 2012;Naeimi and Serio, 2022). We show that TTR aggregates sediment in higher molecular weight fractions occasionally with Hsp104 OE (Figure 3A) and consistently with Hsp104 A503S (Figure 4C).…”
Section: The Formation Of the Ttr Aggregate And The Role Of Hsp104mentioning
confidence: 63%
“…PrDs of humans, also known as transmissible spongiform encephalopathies or TSEs, represent an expanding spectrum of progressive and ultimately lethal neurodegenerative disorders that globally affect about one person out of every one million per year [ 17 , 20 , 49 ]. About 85–90% of all PrDs manifest as the Creutzfeldt–Jakob disease (CJD) or a variant of the CJD (vCJD), with the remainder consisting mainly of the Gerstmann–Straussler–Scheinker (GSS) syndrome, fatal familial insomnia (FFI), variably protease-sensitive prionopathy (vPSPr), and kuru ( ; ; last accessed on 30 August 2022).…”
Section: Prion Disease (Prd) and Prion Neurobiologymentioning
confidence: 99%
“…More importantly, all microbial infections of the brain and CNS contribute to the development of a microbial- and/or viral-induced cytokine storm , which is associated with a progressive inflammatory degeneration of brain cells and tissues. The continuing progression of this cytokine storm is often accompanied by the appearance of amyloid-beta (Aβ) peptides, Aβ amyloid fibers, prion amyloids, related amyloidogenic, lipoprotein or Aβ peptide aggregation processes, the appearance of twisted neurofilamentous structures, including neurofibrillary tangles, pro-inflammatory biomarkers, gliosis of microglial cells, the formation of vacuoles and spongiform change within brain cells, neuronal cell loss, or any combination of these pathological biomarkers associated with a diverse range of human neurological disorders and phenotypic states [ 4 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of yeast biology is the existence of yeast prions—self-perpetuating protein aggregates that confer changes to the yeast’s phenotype and are inherited in a non-Mendelian fashion (for review, see [ 2 ]). Most yeast prion aggregates have amyloid nature, i.e., their prion conformers form long fibrillar structures with a typical regular structure (for review, see [ 3 , 4 , 5 ]).…”
Section: Introductionmentioning
confidence: 99%